Freedom of racist speech Ego and expressive threats. - White, Mark H.; Crandall, Christian
Do claims of "free speech" provide cover for prejudice? We investigate whether this defense of racist or hate speech serves as a justification for prejudice. In a series of 8 studies (N = 1,624), we found that explicit racial prejudice is a reliable predictor of the "free speech defense" of racist expression. Participants endorsed free speech values for singing racists songs or posting racist comments on social media; people high in prejudice endorsed free speech more than people low in prejudice (meta-analytic r = .43). This endorsement was not principled-high levels of prejudice did not predict endorsement of free speech values when identical speech was directed at coworkers or the police. Participants low in explicit racial prejudice actively avoided endorsing free speech values in racialized conditions compared to nonracial conditions, but participants high in racial prejudice increased their endorsement of free speech values in racialized conditions. Three experiments failed to find evidence that defense of racist speech by the highly prejudiced was based in self-relevant or self-protective motives. Two experiments found evidence that the free speech argument protected participants' own freedom to express their attitudes; the defense of other's racist speech seems motivated more by threats to autonomy than threats to self-regard. These studies serve as an elaboration of the Justification-Suppression Model (Crandall & Eshleman, 2003) of prejudice expression. The justification of racist speech by endorsing fundamental political values can serve to buffer racial and hate speech from normative disapproval.
Keywords: Psychology -- Periodicals; Free speech; Justification -- suppression model; Reactance; Prejudice